Effect of Different Mulches on Yeild and Moisture use of Pearl Millet (Pennisetum typhoides) - Daulay, H S; Singh, H P; Singh, R P; Singh, K C (Annals of Arid Zone, 2016)
A field investigation was carried out at the Central Arid Zone Research Institute, Jodhpur. during the kharif season of 1972 and 1973, to find out the most efficient mulch material out of the fourdust, wheat straw, bajra husk and polyethylene, tested for bajra crop. Application of bajra husk and polyethylene gave 25% higher grain yield over control. Crop grown in the mulched plots exhibited higher moisture use efficiency over the mulched control. Besides the mulches were found effective in modifying thermal and moisture regimes conducive to growth and development of pearl millet. When the rainfall distribution was uniform, mulches d:d not how any advantage. Bajra husk, in general, was found to be the cheapest.